An ultrasound method for characterization of viscoelastic properties in frequency domain at small deformations. (December 2021) - Sakhnevych, A; Genovese, A; Maiorano, A; Timpone, F; Farroni, F
Background: The ultrasound technique, usually based on the transmission mode, is capable of providing the viscoelastic properties of polymers. Further techniques involving pulse-echo methods were also described in literature, but they still exhibit inaccuracies in the evaluation of the acoustic properties. Objective: The manuscript focuses on an innovative approach for the characterization of the viscoelastic behavior of polymers employing the ultrasound methodology. The proposed procedure is based on the pulse-echo method in order to overcome possible inaccuracies in acoustic properties evaluation and in issues related to transmitter mode applications. Methods: Starting from the pulse-echo method adopted for the acquisition, a novel formulation for data processing has been developed and described, allowing to determine the wave attenuation coefficient, in comparison to the commonly employed procedures involving ultrasound in polymers characterization, based on transmitter mode inspections. To carry out the study, a specifically designed ultrasound bench has been set up and three different polymers have been tested in the temperature range of interest. Results: According to the proposed methodology, the loss factor towards the temperature is determined starting from the data acquired considering the identified attenuation coefficient and the measured sound velocities. The trustworthiness of the novel procedure has been proved comparing the obtained viscoelastic loss factor quantities to the reference master curves obtained by the standard Dynamic Mechanical Analysis characterizations carried out on the same polymer specimens. Conclusions: A novel methodology involving ultrasound technology aiming to evaluate the viscoelasticity of the polymers using non-destructive approach has been developed. The results obtained are agreement with the standard viscoelastic master curves determined through the DMA.